Proposed new interior design scheme of musical instrument retail at 26-8A,8B,8C,Jln Theatre,30300,Ipoh,Perak for Bentley Music Sdn. Bhd. / Aaron Ashley Awah - Awah, Aaron Ashley (Faculty of Architecture, Planning and Surveying, 2012)
As the musical passion of the Malaysian are growing tremendously. Musical instrument retail is playing one of the important of providing quality and branded instrument to the people. To be able to be stick out in this field, Musical instrument retailers will have to think of a revolutionary idea to overcome the competitive market. This project is to proposed a new branch of Musical Instrument Retail for Bentley Music Sdn. Bhd. at other state instead of Kuala Lumpur, and I have chosen Ipoh, Perak, which located at. The objective of this proposal is to create a new vision of Musical Instrument Store which emphasize of fresh and youthful ideas where most of the Musical instrument store does n o t. On the other hand .solving the spatial arrangement of the shop is also one of my purpose and the anticipating turnout is customer will be satisfied with the retail services and experience a fresh type of musical instrument retail. The reason I doing this project is due to the lack of efficiency of space arrangement in the shop and the dullness of typical musical instrument store. Therefore, a new design is prepare which it may enlighten and satisfy the both the owner, workers and most importantly the customers. A concept that meets the corporate image is highly taken into designing process. And from all the researchdata and details that collected was use as a reference in this design.